Letter to Editor; Coronary Heart disease - Asrar Ali; Babar Ali (Information Technology and Science (ITScience), 2022)
The main risk factors for coronary heart disease (CHD) in adults seem to be influenced, at least in part, by behavioral habits formed in infancy. According to research, teens do not understand the risk for cardiovascular disease and do not believe they are at risk (Vanhecke et al., 2006). Teenagers' longitudinal observations reveal risk factors including obesity remain over time and are connected to the clustering of metabolic syndrome components (Berenson et al., 2005)., According to an Indian study, adolescents from middle- and upper-class families in India have a significant frequency of metabolic and dietary coronary risk factors (Gupta et al., 1998) . In light of this, the current study was conducted to determine the level of risk factor awareness among schoolchildren. The sampling frame consisted of all students enrolled in grades matric through intermediate at the School A in Pakistan.